2007
DOI: 10.1577/t06-012.1
|View full text |Cite
|
Sign up to set email alerts
|

Movement of Walleyes in Lakes Erie and St. Clair Inferred from Tag Return and Fisheries Data

Abstract: Lake Erie walleyes Sander vitreus support important fisheries and have been managed as one stock, although preliminary tag return and genetic analyses suggest the presence of multiple stocks that migrate among basins within Lake Erie and into other portions of the Great Lakes. We examined temporal and spatial movement and abundance patterns of walleye stocks in the three basins of Lake Erie and in Lake St. Clair with the use of tag return and sport and commercial catch-per-unit effort (CPUE) data from 1990 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
92
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(105 citation statements)
references
References 30 publications
12
92
1
Order By: Relevance
“…Using a spatial tag-recovery model and recoveries from a long-term jawtagging study, Vandergoot and Brenden (2014) found that Lake Erie walleyes exhibited age and spatial variability with respect to movement and mortality components. In particular, walleyes in the Lake Erie's western basin were more likely to move to other regions of the lake than eastern basin fish, which was consistent with previous movement studies (Wang et al, 2007;Zhao et al, 2011). Natural mortalities of age-5 and older walleyes were estimated to be lower than those of younger fish in both the lake's western and eastern basins (Vandergoot and Brenden, 2014).…”
Section: Lake Erie Walleye As a Simulation Basissupporting
confidence: 87%
See 2 more Smart Citations
“…Using a spatial tag-recovery model and recoveries from a long-term jawtagging study, Vandergoot and Brenden (2014) found that Lake Erie walleyes exhibited age and spatial variability with respect to movement and mortality components. In particular, walleyes in the Lake Erie's western basin were more likely to move to other regions of the lake than eastern basin fish, which was consistent with previous movement studies (Wang et al, 2007;Zhao et al, 2011). Natural mortalities of age-5 and older walleyes were estimated to be lower than those of younger fish in both the lake's western and eastern basins (Vandergoot and Brenden, 2014).…”
Section: Lake Erie Walleye As a Simulation Basissupporting
confidence: 87%
“…Spatial structuring in the Lake Erie walleye population has been attributed to several factors, including metapopulation dynamics and regional differences in water quality, trophic structure, and incidence of invasive species (Wang et al, 2007;Berger et al, 2012). In addition to functioning as an apex predator (Ryan et al, 2003), walleye support important commercial and recreational fisheries throughout Lake Erie, with fishing activity mostly concentrated in the western and central basins (Roseman et al, 2011;Zhao et al, 2011).…”
Section: Lake Erie Walleye As a Simulation Basismentioning
confidence: 99%
See 1 more Smart Citation
“…Adult walleye migrate throughout the lake and into Lake Huron during summer and fall, but exhibit spawning site fidelity when returning to the four major spring spawning habitats including; Maumee, Sandusky and Detroit Rivers, and an open lake reef complex (Wang et al 2007; Fig. 1).…”
Section: System Descriptionmentioning
confidence: 99%
“…Walleye (Sander vitreus) is a highly vagile species in both riverine and lacustrine environments with dispersal distances exceeding 160 km (Todd and Hass, 1993;Wang et al, 2007). In Lake Erie, longitudinal dispersal of walleye from their primary spawning locations in the western basin appear to be related to size or age (Kershner et al, 1999;Jones et al, 2003;Wang et al, 2007), which could result in differential age composition, and hence age-specific vulnerability patterns, across the lake.…”
Section: Introductionmentioning
confidence: 99%